PENTINGNYA PENDIDIKAN JASMANI BAGI SETIAP PESERTA DIDIK - ., Suharjo (Universitas Negeri Medan, 2015)
Abstract Physical education was learning process to move and learning by moving. In addition to study and theacing with the move for get the purpose learning, in physical education, the student must be move and developing. Developing was through couse purpuse wasn’t aspects of the physical who known is psychomotor, but also developing knowlage and understanding was the ability of cognitive and afective as well as the developing with moving skills, healty and perceptual motors and social emocional. Keywords : Physical Education, Cognitive, Afective and Physicomotor